A Practical Method for Determination of Nine Nucleosides in Tricholoma matsutake by UPLC/MS and Quantitative Analysis of Multicomponents Using Single Marker Method - Li Yong; An-Qin Leng; Zhi-Xiang Yang; Ying Xue (Journal of Analytical Methods in Chemistry)
Nucleosides can be used as quality evaluation indicators of Tricholoma matsutake. In this work, a new ultra-performance liquid chromatography-tandem mass spectrometry (UPLC/MS) strategy for quantitative analysis of multiple components using a single marker (QAMS) was proposed to determine nine nucleosides (adenosine, cytidine, guanosine, inosine, uridine, 2′-deoxyadenosine, 2′-deoxycytidine, 2′-deoxyguanosine, and 2′-deoxyuridine) in T. matsutake. Guanosine was set as the internal reference substance, whose content in T. matsutake was determined using the conventional external standard method. Relative correction factors (RCFs) between guanosine and eight other nucleosides were measured. The concentrations of the eight components were calculated with the obtained RCFs by QAMS. An ultrasonic extraction method is used for sample preparation. This method was validated to be sensitive, precise, and accurate with the LODs of 0.31–1.9 ng, the overall intraday and interday variations less than 4.08%, and the overall recovery over 89.0%. The correlation coefficients (r2) of the calibration curves were higher than 0.9918. The values of vector angle analysis were above 0.99845, which indicates no significant differences between the conventional external standard method and the present QAMS method. As far as we know, this is also the first report of UPLC/MS analysis of nucleoside compounds by QAMS, providing an efficient and feasible quality assessment method for other natural products containing nucleosides.